2023
DOI: 10.1371/journal.pone.0282525
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of vaccine hesitancy for COVID-19, influenza, and pertussis during pregnancy and in mothers of infants under two years: An umbrella review

Abstract: Background Vaccination during pregnancy has been repeatedly demonstrated to be safe and effective in protecting against infection and associated harms for the mother, developing baby, and subsequent infant. However, maternal vaccination uptake remains low compared to the general population. Objectives An umbrella review to explore the barriers and facilitators to Influenza, Pertussis and COVID-19 vaccination during pregnancy and within 2 years after childbirth, and to inform interventions to encourage uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 96 publications
1
5
0
Order By: Relevance
“…The predictors of COVID-19 vaccine hesitancy in the study by Kigongo et al were perceived low risk of COVID-19 infection, vaccine side effects, and negative beliefs towards vaccine [ 157 ], whereas in this synthesis, no influenza vaccine, mistrust of vaccine, complacency, pregnancy, being female, and safety concerns were predictor of VH. However, factors similar to the ones identified in this synthesis were also identified in other studies [ 163 , 164 , 165 , 166 ]. These discrepancies may be because factors change with time, place, and culture as well as being psychologically- and context-specific [ 167 ].…”
Section: Discussionsupporting
confidence: 86%
“…The predictors of COVID-19 vaccine hesitancy in the study by Kigongo et al were perceived low risk of COVID-19 infection, vaccine side effects, and negative beliefs towards vaccine [ 157 ], whereas in this synthesis, no influenza vaccine, mistrust of vaccine, complacency, pregnancy, being female, and safety concerns were predictor of VH. However, factors similar to the ones identified in this synthesis were also identified in other studies [ 163 , 164 , 165 , 166 ]. These discrepancies may be because factors change with time, place, and culture as well as being psychologically- and context-specific [ 167 ].…”
Section: Discussionsupporting
confidence: 86%
“…These findings were also found among teachers in Poland, 12 Greece 14 and America, 15 and were similar to results from the study of HCWs, 46 elders, 47 and other group of people. 48 , 49 A belief in the efficacy and safety of vaccines was a sign of vaccine confidence. 50 Increasing vaccine confidence could increase acceptance of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on factors influencing vaccination decision-making during pregnancy suggest that healthcare professional (HCP) recommendations and beliefs about vaccine safety and efficacy are key drivers of vaccination uptake [53][54][55]. However, the impact of HCP recommendations could be diminished by factors such as belief in vaccine-induced harm, particularly for novel vaccines like COVID-19 [54,56,57].…”
Section: Plos Onementioning
confidence: 99%
“…Recent qualitative research has identified belief in conspiracy theories and misinformation as obstacles to vaccine uptake among pregnant women [56]. Previous systematic reviews have mainly included quantitative methodologies [53] and may have focused less on the complexity, context, nuance and meaning of vaccinations in pregnancy. Our study aims to fill this knowledge gap.…”
Section: Plos Onementioning
confidence: 99%